Challenges and Opportunities in the Implementation of the Teacher Mobilization Program: An Analysis from the Resource Perspective - Prihatin, Eka; Kurniatun, Taufani C.; Hartini, Nani; Rahyasih, Yayah (Indonesian Research Journal in Education |IRJE|, 2024)
This study analyzes the effectiveness of the Teacher Mobilization Program (PGP) by the Ministry of Education, Culture, Research, and Technology, focusing on resource-related challenges and opportunities. Using a descriptive qualitative method, data were collected from ten PGP alumni and the coordinator of the Directorate of Professional Education and Development of Teachers and Education Personnel (PPPGTK). Findings indicate that while communication strategies align with Edward III’s indicators, areas need improvement. The program meets ideal resource characteristics but faces challenges like inadequate infrastructure in remote areas. Implementer attitudes are crucial, with incentives and bureaucratic appointments identified as key areas for improvement. Flexible Standard Operating Procedures (SOPs) support effective implementation, though organizational fragmentation can hinder coordination. Recommendations include clear communication of program objectives from registration, ensuring training does not overlap with teaching hours, and developing a follow-up action plan. These measures aim to optimize resource utilization and enhance PGP’s overall effectiveness.